Od najpomembnejših k najbolj ilustrativnim avtorjem - Marinčič, Katarina (Vestnik za tuje jezike, 2012)
The article discusses some new approaches to teaching literature and literary history in the digital age. In an era when access to primary as well as to secondary literature is no longer an exclusive privilege, the teacher, free of the obligation to provide essential information, should instead provide the students with means of orientation. In this aim, typical, illustrative texts of (relatively) minor authors (such as Théophile Gautier) should be read and discussed in class besides the works belonging to the literary canon.
Keywords: Gautier, Théophile, 1811-1872; francoska književnost; French literature; Romanticism; romantika; didactic method; didaktika; metodika; književna didaktika